直线共轭内啮合齿轮泵困油的参数影响分析 - 王郑力; 张振山; 张方方; 刘佳 (Jixie chuandong)
The gear pair meshing process of the straight conjugate internal gear pump is analyzed, by using tangent polar coordinate method,based on the meshing angle function,the formulation for calculating trapping volume are deduced,and it is affirmed through UG modeling measurement. Then,by using MATLAB programming,the effect of the gear basic parameters on trapping oil characteristic of NBX3pump is analyzed,got the following conclusions:the bigger addendum circle radius of internal gear,tooth profile half-angle,arc tooth thichness of pitch circle angle and smaller addendum circle radius of straight gear is useful to decreasing the adverse effect of trapping oil phenomenon.